Światowe zużycie energii pierwotnej oraz zapotrzebowanie na nią w przyszłości - Olkuski, Tadeusz (Polityka i Społeczeństwo, 2020)
In the developing world, the demand for energy is constantly growing. Most scenarios of economic development in the world predict an increase in demand for fuels and energy. For example, in the New Policy Scenario developed by the International Energy Agency, an increase in the share of natural gas and renewable energy in primary energy demand is assumed. Not only highly developed countries expect an increased demand in this area, also developing countries, mainly from Asia, will need more fuels and energy in the future. The main development engines will be China and India. It is these countries that will need the most raw materials and energy. Poland is also planning further economic development, but the continued lack of energy policy does not allow for the accurate assessment of future needs in this area.